PENGARUH STRES KERJA DAN PENGEMBANGAN KARIR TERHADAP KINERJA PEGAWAI KANTOR DINAS PENGENDALIAN PENDUDUK DAN KELUARGA BERENCANA (DP2KB) KABUPATEN LABUHANBATU - Amalinda, Rica; Nasution, Ade Parlaungan (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2020)
The purpose of this study was to determine the effect of work stress and career development on the performance of the employees of the Office of Population Control and Family Planning (DP2Kb) Labuhanbatu Regency. This study used a questionnaire with a measurement scale using a Likert scale which was analyzed using validity, reliability, and multiple linear regression analysis using SPSS 20. The population in this study was 38 people and the sample in this study was the entire population of 38 people taken using Saturated Sample method. The results of this study indicate that work stress and career development simultaneously have a positive and significant effect on the performance of the office employees Population Control and Family Planning (DP2KB) Labuhanbatu. With the value of Fcount> Ftable, namely 10.566> 3.27 and a significant value of 0.000 <0.05.